2019
DOI: 10.1039/c9ra05740d
|View full text |Cite
|
Sign up to set email alerts
|

Electrochemical and adsorption behaviors of thiadiazole derivatives on the aluminum surface

Abstract: Electrochemical and adsorption behaviors of thiadiazole derivatives on the aluminum surface were investigated by an experimental and quantum chemical approach.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 52 publications
2
6
0
Order By: Relevance
“…In this study, C–OH bond was strongly shifted toward higher values as deconvoluted at 288.46 eV, due to the electronic interactions between the inhibitor and the copper surface. [ 44 ] This result was in accordance with the prediction that the hydroxyl from CA absorbed on the surface of copper due to its strong polarity and prevented contact between the corrosive medium and copper.…”
Section: Resultssupporting
confidence: 89%
“…In this study, C–OH bond was strongly shifted toward higher values as deconvoluted at 288.46 eV, due to the electronic interactions between the inhibitor and the copper surface. [ 44 ] This result was in accordance with the prediction that the hydroxyl from CA absorbed on the surface of copper due to its strong polarity and prevented contact between the corrosive medium and copper.…”
Section: Resultssupporting
confidence: 89%
“…There exists a 'wide palette' of approaches on how to achieve a superhydrophobic surface [20], such as the sol-gel method, electrospinning, electrochemical methods, and layerby-layer method, which can be found in various review articles, like Darband et al [21] and Guo et al [22]. It has been confirmed that surfaces with hydrophobic properties can be an effective corrosion protection for numerous types of metal, such as steel [11,19,[23][24][25][26][27][28][29][30][31], copper [10,[32][33][34][35][36][37], nickel [38], zinc [39,40] Al-alloys [41][42][43][44][45][46] and Mg-alloys [47][48][49][50][51]. Carboxylic acids have been used to create hydrophobic surfaces on many different metal substrates [52][53][54][55].…”
Section: Introductionmentioning
confidence: 99%
“…When compared to the reported inhibitors, such as thiazole derivatives, coumarin derivatives and other heterocyclic compounds, coumarin with a small molecular volume exhibits a small steric hindrance, which weakens its ability to repel corrosive ions. 6,7,11,33 Thus, the inhibition efficiency of coumarin occurs in a high concentration.…”
Section: Discussionmentioning
confidence: 99%
“…These current perturbances were generally considered as the proof of protective lm rupture and their re-building at the metallic surface, reecting the nucleation and growth of pitting. 30,31 These transient changes of current density caused the generation of metastable pits at surface, [32][33][34] thereinto, some of pits would repassivate immediately, but the others would continue to grow and ultimately cause damage to the metallic surface. 35 It was supposed that the instability of this lm was concerned with the adsorption of coumarin on the surface.…”
Section: Polarization Curvesmentioning
confidence: 99%